Characteristics of Laminated Bamboo Lumber Glued with Tannin Resorcinol Formaldehyde - Ignasia M Sulastiningsih; Adi Santoso; Barly Barly; Mohamad I Iskandar (Masyarakat Peneliti Kayu Indonesia, 2013)
The objective of this study were to determine the characteristics of laminated bamboo lumber (LBL) glued with tannin resorcinol formaldehyde with particular focus on the effects of varying pre-treatment of bamboo strips and extender content on the properties of LBL. Bamboo strips for LBL fabrication were prepared from mature culms of andong bamboo (Gigantochloa pseudoarundinaceae). The strips were assigned into 4 groups by pre-treatment methods: untreated, cold soaking in 5% boron solution for 2 hours, bleached with 17.5% H2O2 solution, and bleached with 20% H2O2 solution. The LBL was manufactured using tannin resorcinol formaldehyde (TRF) added with extender at 4 levels equal to 0, 2.5, 5, and 10% of TRF. The cold pressing time applied was 4 hours. The results showed that the average density, moisture content, thickness swelling, bending strength and bonding strength of LBL produced were 0.77 g cm-3, 8.9%, 5.2%, 1146 kg cm-2, and 51.5 kg cm-2 respectively. No delamination occurred in all samples which indicating high bonding quality. There was strong interaction between pre-treatment of bamboo strips and extender content in affecting some properties of LBL. In general three-layer thick LBL glued with tannin resorcinol formaldehyde adhesive had strength values similar to wood strength class I. Laminated bamboo lumber is suitable for wood substitute especially for furniture material.Key words: extender, laminated bamboo lumber, pre-treatment, tannin resorcinol formaldehyde